Kriminalisasi Praktik Perkawinan Tidak Tercatat yang Berdampak pada Kerugian Perempuan dan Anak - Denni Rade Situmeang; Isfandir Hutasoit; Edwar Kelvin (Dinasti Research, 2026)
This study discusses the criminalization of unregistered marriage practices (nikah sirri) that result in legal harm to women and children from the perspective of Indonesian criminal law. The main issue examined in this research is the legal status of unregistered marriages within the Indonesian legal system and the extent to which such practices can be criminalized under the new Criminal Code (KUHP). The method used is normative legal research with statutory, conceptual, and case approaches, conducted through library research on primary and secondary legal materials. The findings show that normatively, the Marriage Law requires marriage registration as an administrative requirement to provide legal certainty and protection. However, in practice, many unregistered marriages still occur, causing uncertainty regarding the legal status of wives and children, particularly in relation to maintenance rights, inheritance, and population administration. The new Criminal Code does not explicitly criminalize nikah sirri, but it provides criminal sanctions for accompanying acts such as document forgery, marriages conducted despite legal impediments, and child marriages. This study also finds a shift in the paradigm of criminal law, which has begun to enter the private sphere of the family as a form of protection for women and children. Nevertheless, caution is needed in the implementation of criminalization to avoid over-criminalization and the blurring of boundaries between criminal law and administrative law. Therefore, strengthening legal policies that balance administrative and criminal approaches is important to provide more effective and equitable legal protection for vulnerable groups.